Mechanics of Biological Tissue - Holzapfel, Gerhard A.; Ogden, Ray W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
The mechanics of biological tissues is a multidisciplinary and rapidly expanding area of research. This book highlights some important research directions that combine mechanical sciences with exciting new developments in biology. It includes state-of-the-art articles on: Tissue growth and remodelling – general continuum theories of growth, remodelling and adaptation, with specific applications to arterial, tendon and cartilage growth and to bone healing. Micromechanics, cells and matrix – measurements of the mechanical properties of cells, engineering of cell systems, constitutive and computational modelling of cells and cell-substrate interactions, and the transition from microscopic modelling to its macroscopic consequences. Arteries in health and disease – analysis of residual stress and its development, modelling the constitutive properties of arterial walls, computational analysis of the effect of stenting on the arterial wall, studies of collagen fibre distributions in saccular aneurysms and the interaction between blood flow and aneurysm development. Biological tissues – the musculo-skeletal system, heart valves, ligaments, intervertebral discs, the uterus and vocal fold tissues, with experimental, modelling and computational perspectives. Image-based analysis – illustration of imaging techniques that have great potential for the analysis of tissue properties and pathologies and for guiding the design of engineered tissue constructs. This collection of papers should be of interest to theoretical, computational and experimental researchers and doctoral students in the area of biomechanics and in related areas of engineering, biology and medicine.
Tissue Growth and Remodelling -- Towards a Theory of Vascular Growth and Remodeling -- Complementary Roles of Theoretical Modeling and Computer-controlled Experimentation in Vascular Growth and Remodeling -- On the Modeling of Growth and Adaptation -- Growth in Soft Biological Tissue and Residual Stress Development -- Characterization and Modeling of Growth and Remodeling in Tendon and Soft Tissue Constructs -- Modeling and Simulation of Remodeling in Soft Biological Tissues -- Anisotropic Remodelling of Biological Tissues -- A Mechanobiological Formulation of Bone Healing -- Continuum Models of Growth with Emphasis on Articular Cartilage -- Micromechanics, Cells and Matrix -- Tensile Properties and Local Stiffness of Cells -- Microfluid-dynamics in Three-dimensional Engineered Cell Systems -- Nonlinear Constitutive Models for Cochlear Outer Hair Cells -- Prediction of Changes in Cell-substrate Contact under Cyclic Substrate Deformation Using Cohesive Zone Modelling -- Micromechanics and Macromechanics of the Tensile Deformation of Nacre -- Arteries in Health and Disease -- Mechanical Properties of Atherosclerotic Tissues -- Towards a Computational Methodology for Optimizing Angioplasty Treatments with Stenting -- Computational Modeling of Stented Arteries: Considerations for Evolving Stent Designs -- Simulation of In-stent Restenosis for the Design of Cardiovascular Stents -- Material Property Alterations with Early Atheroma in an Animal Model -- Microscopic Analysis of Residual Stress and Strain in the Aortic Media Considering Anisotropy of Smooth Muscle Layer -- Parameter Identification in Arteries Using Constraints -- Collagen Organization and Biomechanics of the Arteries and Aneurysms of the Human Brain -- Image-based Simulation of Blood Flow and Arterial Wall Interaction for Cerebral Aneurysms -- Biological Tissues -- A Framework for Soft Tissue and Musculo-skeletal Modelling: Clinical Uses and Future Challenges -- Invariant Formulation for Dispersed Transverse Isotropy in Tissues of the Aortic Outflow Tract -- Mathematical Modelling of Cardiac Mechanoenergetics -- Creep and Relaxation in Ligament: Theory, Methods and Experiment -- Viscoelastic Constitutive Law Based on the Time Scale of the Mechanical Phenomena -- A Coupled FE Analysis of the Intervertebral Disc Based on a Multiphasic TPM Formulation -- Is the Free Energy of Hydrogel the Sum of Elastic Energy and Ionic Energy? -- In Vivo Experiments to Characterize the Mechanical Behavior of the Human Uterine Cervix -- Viscoelastic Response of Vocal Fold Tissues and Scaffolds at High Frequencies -- An Alternative Fabric-based Yield and Failure Criterion for Trabecular Bone -- Image-based Analysis -- Functional Micro-imaging at the Interface of Bone Mechanics and Biology -- Strain Measurement Using Deformable Image Registration -- Image-based Hierarchical Analysis and Design of Tissue Engineering Scaffolds.
Keywords: Mechanics; Mechanics, Applied; Computer mathematics; Amorphous substances; Complex fluids; Solid Mechanics; Computational Science and Engineering; Soft and Granular Matter, Complex Fluids and Microfluidics